Pengaruh Jumlah Produksi dan Harga terhadap Nilai Ekspor Kakao Indonesia Tahun 2017-2020 - Nidaul Izzah; Dennysa Damayanti (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2023)
Cacao is one of the plantation commodities playing an important role in Indonesian economic activities. Cacao also makes a significant contribution to Indonesia’s foreign exchange income. The research aims to identify the impact of total cacao production and price, and total production and price on Indonesian cacao export values from 2017 to 2020. The type of research used was explanatory research with a quantitative approach. The data in the research were secondary data collected from Indonesian Statistics (BPS). Samples in the research were collected through nonprobability sampling using the saturated sampling method. The statistical testing with t-test showed that total production as determined by the cacao total production had a significant value of 0.000 and was less than the significance level of 0,05. The cacao selling price (X2) was 0.000 with a significant value of less than 0.05 or 0.000 < 0,05. Therefore, Ha accepted, the price variable affected export volume significantly. The F-test showed an F value of 135.981 with a significance level of 0.000, and since it is less than 0.05 therefore a conclusion can be drawn that production and price jointly affected the variable independents. The value of the R square determinant coefficient showed the value of export-dependent 0,862 value that can be explained by the independent variables of production and price which was 86.2% and 13,8%, respectively. The government is expected to increase cacao productivity by providing supporting facilities for cacao farmers in Indonesia.